THE IMPLEMENTATION OF DISCOVERY LEARNING (DL) MODEL TO IMPROVE THE SECOND GRADERS’ MATHEMATICAL CONCEPTS UNDERSTANDING ON COMPARING NUMBER MATERIALS AT SDN BALAGEDOG III - Fuji Alfiani; Faridillah Fahmi Nurfurqon; Muhamad Ghiyats Ristiana (xxxx-xxxx, 2022)
This research was motivated by the low score of second grade students' test results on the matter of comparing numbers. This study aims to describe the Discovery Learning model that is implemented to solve the problem of students' low mathematical comprehension abilities in the matter of comparing numbers. The research was carried out in November 2022 with the research subjects being class II students, totaling 23 students, consisting of 16 male students and 7 female students. This study uses the Classroom Action Research method with the Stephen Kemmis and Robyn McTaggart models with two cycles, each cycle consisting of four stages, namely: planning, action, observation, and reflection. The pre-cycle percentage based on the results of the conceptual understanding assessment was 52% of students whose scores were above the minimum completeness criteria (KKM), then in cycle I it increased to 74% of students whose scores were above the KKM, and in cycle II it also increased to 96%. . These data indicate that using the Discovery Learning model can improve students' understanding of mathematical concepts in the mathematics subject matter of comparing numbers